(untitled) (AYUSHDHARA, 2021)
In present time, lifestyle disorders are rapidly rising in our society. Over consumption of food, alcohol and fructose sweetened soft drinks in combination with a sedentary lifestyle has resulted in increased prevalence of visceral obesity, metabolic syndrome and gout in all socioeconomic groups of society including the lower socioeconomic status. Gout is one of the major life style disorders. The clinical manifestation and textual references of gout may be attributed with ’Vatarakta’, also known as Vatashonita. Vata and Rakta are the Dosha and Dushya respectively which are primarily involved in the pathology of Vatarakta. Virudhaahar and Vihara aggravate Vata dosha and Rakta dhatu. Provocated Vata gets Aavrut with vitiated Rakta dhatu leading to the beginning of pathophysiological cascade of Vatarakta. The patients for this study were diagnosed based on Ayurvedic and modern parameters. Clinical signs and symptoms described in classical texts were considered for the diagnosis of Vatarakta, whereas serum uric acid was considered as investigation based diagnostic tool. Total 15 patients were registered in trial. The selected patients were given the trial drug i.e., Amrita guggulu one gram and Guduchi kwath 50ml twice a day with plain water after food. Out of 15 registered patients, 1 dropout from the trial, 4 patients (28.57%) showed marked improvement, 7 patients i.e., 50% showed moderate improvement and 3 patients 21.43% showed mild improvement. None of patient in present clinical trial remained unimproved or deteriorated during the clinical trials. In the present study, none of the patient reported any adverse effect to the trial drug during study and follow up period.